In vitro Characteristics of Heterogeneous Equine Hoof Progenitor Cell Isolates - Yang, Qingqiu; Pinto, Vanessa Marigo Rocha; Duan, Wei; Paxton, Erica E.; Dessauer, Jenna H.; Ryan, William; Lopez, Mandi J. (Frontiers in Bioengineering and Biotechnology, 2019)
Damage to an ectodermal-mesodermal interface like that in the equine hoof and human finger nail bed can permanently alter tissue structure and associated function. The purpose of this study was to establish and validate in vitro culture of primary progenitor cell isolates from the ectodermal-mesodermal tissue junction in equine hooves, the stratum internum, with and without chronic inflammation known to contribute to lifelong tissue defects. The following were evaluated in hoof stratum internum cell isolates up to 5 cell passages (P): expansion capacity by cell doublings and doubling time; plasticity with multi-lineage differentiation and colony-forming unit (CFU) frequency percentage; immunophenotype with immunocytochemistry, and flow cytometry; gene expression with RT-PCR; and ultrastructure with transmission electron microscopy. The presence of keratin (K)15 and K19 as well as cluster of differentiation (CD)44 and CD105 was determined in situ with immunohistochemistry. To confirm in vivo extracellular matrix (ECM) formation, cell-scaffold (polyethylene glycol/poly-L-lactic acid and tricalcium phosphate/hydroxyapatite) constructs were evaluated with scanning electron microscopy 9 weeks after implantation in athymic mice. Cultured cells had characteristic progenitor cell morphology, expansion, CFU frequency percentage and adipocytic, osteoblastic, and neurocytic differentiation capacity. CD44, CD105, K15, and K19 proteins were present in native hoof stratum internum. Cultured cells also expressed CD44, CD105, K14, K15 proteins in addition to CD29, K19, and desmogleins 1 and 3. Gene expression of CD105, CD44, K14, K15, sex determining region Y-box 2 (SOX2) and octamer-binding transcription factor 4 (OCT4) was confirmed in vitro. Cultured cells had large, eccentric nuclei, elongated mitochondria, and intracellular vacuoles. Scaffold implants with cells contained fibrous ECM 9 weeks after implantation compared to little or none on acellular scaffolds. In vitro expansion and plasticity and in vivo ECM deposition of heterogeneous, immature cell isolates from the ectodermal-mesodermal tissue interface of normal and chronically inflamed hooves are typical of primary cell isolates from other adult tissues, and they appear to have both mesodermal and ectodermal qualities in vitro. These results establish a unique cell culture model to target preventative and restorative therapies for ectodermal-mesodermal tissue junctions.